Hydroxylation of Phenol by an Azomethine Quinoxaline Schiff Base Copper (II) Complex - Arun, Vasudevan (Current Catalysis, 2024)
IntroductionA binuclear azomethine quinoxaline Schiff base copper (II) complex, [Cu2LCl2], having square-planar environment around each copper (II), has been synthesized.MethodsThe coordination of the azomethine quinoxaline Schiff base with copper (II) and its structure was studied by various physicochemical and spectroscopic measurements.ResultsCatalytic activity of this complex in phenol hydroxylation reaction has been examined using H2O2 as a green oxidant.ConclusionCatalytic reaction conditions were optimized and under these conditions, 18.32 % conversion of phenol has been obtained for this catalyst
Keywords: diaminomaleonitrile